THE EFFECT OF LITERACY, AND PRODUCT UNDERSTANDING ON STUDENTS' INTEREST IN CONDUCTING TRANSACTIONS IN ISLAMIC FINANCIAL INSTITUTIONS, RELIGIOSITY AS AN INTERVENING VARIABLE - Bara, AL; Pradesyah, Riyan (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to see the influence of literacy and product understanding on students' interest in making transactions in Islamic financial institutions, with religiosity as an intervening variable. The religiosity variable is an intermediate variable, which is predicted to strengthen or weaken the literacy and product understanding variables for students' interest in making transactions in Islamic financial institutions. Where as is known, religiosity can balance between people's thinking and understanding, related to students' interest in making transactions in Islamic financial institutions. Data collection was carried out in the study, by distributing questionnaires, and the analysis tool used was Smart PLS. As for the results obtained, Literacy has no effect on Interest through Religiosity as an intervening variable. Meanwhile, Product Understanding has a significant effect on Interest through Religiosity as an intervening variable.